Searching Before It Is Too Late: A Survey of Blood Parasites in Ctenosaura melanosterna, a Critically Endangered Reptile of Honduras. (28th November 2012) - Davis, Andrew K.; Benz, Andrew C.; Ruyle, Leslie E.; Kistler, Whitney M.; Shock, Barbara C.; Yabsley, Michael J.
Abstract : For species at risk of extinction, any parasites they have would be expected to face a similar fate. In such cases, time is running out for efforts to identify and study their parasitic fauna before they are gone. We surveyed the hemoparasite fauna of 50 black-chested, spiny-tailed iguanas ( Ctenosaura melanosterna ), a critically-endangered species, on an island off the coast of Honduras. Blood samples from captured animals were tested for hemoparasites by thin blood smear and molecular analyses. Based on microscopy, two parasites were identified, a Plasmodium sp. in 14% of iguanas and a Hepatozoon sp. in 32%. For both parasites, parasitemia levels were <0.1%. Prevalence and parasitemias of Hepatozoon declined with increasing host size, a pattern differing from most prior studies of saurian reptiles. From a subset of iguanas with microscopy-confirmed Plasmodium infections, sequence analysis of 454 bp of the cytochrome b gene indicated that the Plasmodium species was distinct from known Plasmodium and was most closely related to P. chiricahuae (96.5% similarity) followed by P. mexicanum (95.8% similarity). Efforts to amplify the Hepatozoon parasite using PCR were not successful. Additional surveys and studies of this host-parasite system would be valuable, both to science and to the management of this endangered animal.